Thinker's Sign - Eduardo Smelin Perdomo Domínguez; Héctor M. Ramos-Zaldívar (Annals of Internal Medicine: Clinical Cases)
Thinker's sign, also called the Dahl sign, is a dermatologic sign of chronic obstructive pulmonary disease (COPD), characterized by hyperpigmented, bilateral, callused patches triggered by continuous tripod posture. It also can be associated with bilateral hyperkeratosis and hyperpigmentation of the forearms and elbows. Although the incidence of thinker's sign in severe COPD has not been well established, its potential diagnostic value is worth noting, as it can unmask the magnitude of the underlying disease. We report the case of a Honduran Garifuna woman with thinker's sign on both thighs and elbows, associated with clinical features of COPD.